PENGELOLAAN PENDAPATAN ASLI DAERAH DALAM PERSEPEKTIF KEUANGAN PUBLIK ISLAM DI BAKEUDA KEBUPATEN TEBO - Rihadatul Aisi; Elyanti Rosmanidar (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to determine the management of Tebo Regency's Original Regional Income and the factors that cause the decline in Tebo Regency's PAD. This study uses a qualitative approach with a descriptive study type. Data collection techniques are carried out through observation, interviews and documentation from local government employees, MUI figures, and the community. The collected data are analyzed using the Miles and Huberman interactive analysis model, which includes the stages of data reduction, data presentation, and drawing conclusions. This study concludes that the management of Original Regional Income (PAD) in Tebo Regency has reflected the application of good financial governance principles according to the perspective of Islamic public finance and Mahmudi's theory. This can be seen from the consistency of the application of the principles of justice, efficiency, effectiveness, transparency, accountability, independence, and legal certainty in regional fiscal policy. Although there has been progress, the low PAD is still influenced by the less than optimal utilization of local economic potential, weak quality of the apparatus, low community compliance, and an administration system that has not been integrated. In the Islamic perspective, the practice of managing PAD has also been based on the values of faith, honesty, trustworthiness, tabligh, and intelligence, which reflect moral responsibility to Allah SWT and society. Therefore, increasing PAD in the future requires structural reform, fiscal education, strengthening technology, and broader public participation in order to realize healthy, fair, and sustainable regional finances.